2016
DOI: 10.1016/j.cub.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The Expensive Germline and the Evolution of Ageing

Abstract: The trade-off between survival and reproduction is the bedrock of the evolutionary theory of ageing. The reproductive system regulates ageing of the soma, and removal of germ cells extends somatic lifespan and increases resistance to a broad variety of abiotic and biotic stresses. The general explanation for this somatic response is that reduced reproduction frees up resources for survival. Remarkably, however, the disruption of molecular signaling pathways that regulate ageing increases lifespan without the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
216
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(231 citation statements)
references
References 110 publications
(170 reference statements)
14
216
1
Order By: Relevance
“…Our findings suggest an additional trade-off between progeny quantity and quality in that DR mothers produce fewer but larger progeny that cope better with early-life starvation. These observations demonstrate the importance of progeny quality as an additional metric for reproductive fitness [57]. …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings suggest an additional trade-off between progeny quantity and quality in that DR mothers produce fewer but larger progeny that cope better with early-life starvation. These observations demonstrate the importance of progeny quality as an additional metric for reproductive fitness [57]. …”
Section: Discussionmentioning
confidence: 98%
“…Reproduction is typically thought to occur at the expense of somatic maintenance and lifespan [18,57]. Using fecundity as a proxy for reproductive output simplifies analysis of this putative trade-off, but it does not fully reflect biological complexity.…”
Section: Discussionmentioning
confidence: 99%
“…As selection then seeks to optimize reproductive success rather than longevity, and as limited resources enforce a compromise between investment in reproduction and somatic maintenance, reproduction thereby triggers ageing and entails costs to individuals [1,2]. The result is generally, though not universally [36], a trade-off or negative association between fecundity and longevity [2,7]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the discoveries of environmental interventions that dramatically increase healthy lifespan in model organisms without the cost of reduced reproduction have challenged the current paradigm and suggested that our understanding of the evolution of ageing is incomplete (Dillin et al. ; Kenyon ; Antebi ; Gems and Partridge ; Maklakov and Immler ; Flatt and Partridge ). Specifically, experimental downregulation of nutrient‐sensing insulin/IGF‐like (IIS) signaling pathway that governs biosynthesis in response to nutrient availability can achieve increased longevity without a concomitant decrease in reproduction in model organisms (Dillin et al.…”
mentioning
confidence: 99%